Analisis Perubahan Kualitas Batubara Sebelum dan Sesudah Swabakar di Stockpile 10 Port Paring Lahung - Mellysa Caldera; Deddy Nan Setya Putra Tanggara; Dody Ariyantho Kusma Wijaya; I Putu Putrawiyanta; Yos David Inso (Pusat riset dan Inovasi Nasional, 2025)
Coal is an important energy source that is still widely used in industry, especially the power generation industry, because of its high energy content. However, in the process of handling and storage, coal has the characteristic of being easily oxidized, This oxidation process, if it occurs continuously, can cause internal heat accumulation which eventually triggers spontaneous combustion. This study aims to analyze changes in coal quality before and after spontaneous combustionto find out how spontaneous combustionaffects coal quality in stockpiles. The research method used is a quantitative method where the data from laboratory tests on coal quality before and after spontaneous combustionis analyzed, the comparison of coal quality in stockpile 10 before and after spontaneous combustionis then graphed to see changes in the quality of each parameter. Based on the results of the analysis of changes in coal quality before and after spontaneous combustion, there were significant changes to several coal quality parameters, namely Total Moisture which was originally from 7.06% to 5.50% (down by 1.56%), Moisture which was originally 3.91% to 3.22% (down by 0.69%), Ash Content which was originally 8.84% to 14.67% (up by 5.83%), Volatile Matter which was originally 39.77% to 35.10% (down by 4.67%), Fixed Carbon from 47.48% to 47.01% (down by 0.47%), Sulphur from 0.55% to 0.46% (down by 0.9%), and Calorific value decreased from 6,921 to 6,289 kcal/kg (down by 632 kcal/kg). This decrease in quality has a direct effect on the selling value and efficiency of coal combustion. The existence of an analysis of changes in coal quality due to spontaneous combustioncan help companies to find out how much of an impact losses can be caused by the occurrence of spontaneous combustion. By considering the potential losses due to spontaneous combustion, the company will make efforts to prevent the occurrence of spontaneous combustion in the future to minimize the losses caused.